Historical notes on media criticism (Novos Olhares, 2016)
Influenced by North-American standards, the press criticism’s practicein Brazil has already had a short history. If, in practice, such initiatives are rareand sporadic, much rarer are the Brazilian studies on this topic. This essay aimsto organize historical notes on media criticism in the country. The intention is,based on these notes, reflect the need to study the press review as a researchand teaching field.